ZIPCO, a putative metal ion transporter, is crucial for Plasmodium liver‐stage development. Issue 11 (25th September 2014) - Sahu, Tejram; Boisson, Bertrand; Lacroix, Céline; Bischoff, Emmanuel; Richier, Quentin; Formaglio, Pauline; Thiberge, Sabine; Dobrescu, Irina; Ménard, Robert; Baldacci, Patricia
Abstract The malaria parasite, Plasmodium, requires iron for growth, but how it imports iron remains unknown. We characterize here a protein that belongs to the ZIP (Zrt‐, Irt‐like Protein) family of metal ion transport proteins and have named ZIP domain‐containing protein (ZIPCO). Inactivation of the ZIPCO‐encoding gene in Plasmodium berghei, while not affecting the parasite's ability to multiply in mouse blood and to infect mosquitoes, greatly impairs its capacity to develop inside hepatocytes. Iron/zinc supplementation and depletion experiments suggest that ZIPCO is required for parasite utilization of iron and possibly zinc, consistent with its predicted function as a metal transporter. This is the first report of a ZIP protein having a crucial role in Plasmodium liver‐stage development, as well as the first metal ion transporter identified in Plasmodium pre‐erythrocytic stages. Because of the drastic dependence on iron of Plasmodium growth, ZIPCO and related proteins might constitute attractive drug targets to fight against malaria.